Capacity Building for Traditional Market Traders through Sales Optimization and Financial Management Training in Watutumou-2 Village - Agus Supandi Soegoto; Bode Lumanauw; Deasy Soeikromo; Andini Pratiwi Soegoto; Andi Wiratama Satriani (Media Publikasi Cendekia Indonesia, 2026)
Traditional markets face significant threats from modern markets and e-commerce due to superior management and technology. The decline in the number of buyers has resulted in a decrease in the number of traditional markets in various regions. This Community Partnership Program (PKM) aimed to enhance the competitiveness of traders in Watutumou-2 Village, North Minahasa, through Sales Optimization and Financial Management Training. The program involved 29 participants and utilized a multi-stage method: lectures/counseling, hands-on training, and intensive mentoring. Results indicated a significant success rate, with 95% of the 29 participants (including 25 traders and 4 stall owners) being able to understand and apply the materials. Notably, the mentoring stage encouraged in mindset shift and practice. Traders began rearranging product layouts to attract buyers and adopting digital financial recording via smartphones. This program proves that integrated training and mentoring can effectively transform traditional trading patterns into professional business management